Cloning and Functional Analysis of Sucrose:Sucrose 1-Fructosyltransferase from Tall Fescue - Lüscher, Marcel (American Society of Plant Physiologists, 2000)
Enzymes of grasses involved in fructan synthesis are of interest since they play a major role in assimilate partitioning and allocation, for instance in the leaf growth zone. Several fructosyltransferases from tall fescue (Festuca arundinacea) have previously been purified (Lüscher and Nelson, 1995). It is surprising that all of these enzyme preparations appeared to act both as sucrose (Suc):Suc 1-fructosyl transferases (1-SST) and as fructan:fructan 6(G)-fructosyl transferases. Here we report the cloning of a cDNA corresponding to the predominant protein in one of the fructosyl transferase preparations, its transient expression in tobacco protoplasts, and its functional analysis in the methylotrophic yeast, Pichia pastoris. When the cDNA was transiently expressed in tobacco protoplasts, the corresponding enzyme preparations produced 1-kestose from Suc, showing that the cDNA encodes a 1-SST. When the cDNA was expressed in P. pastoris, the recombinant protein had all the properties of known 1-SSTs, namely 1-kestose production, moderate nystose production, lack of 6-kestose production, and fructan exohydrolase activity with 1-kestose as the substrate. The physical properties were similar to those of the previously purified enzyme, except for its apparent lack of fructan:fructan  6(G)-fructosyl transferase activity. The expression pattern of the corresponding mRNA was studied in different zones of the growing leaves, and it was shown that transcript levels matched the 1-SST activity and fructan content.